Factors Influence the Development of Dysrhythmia after Acute Myocardial Infarction in Patients Admitted to CCU of Alkindy Teaching Hospital - Salman, Mohammed Abdul Jabbar; Kubba, Rushd i A.H.; Oleiwi, Hamzah Qoneed; Oleiwi, Hamzah Qoneed; Khazaal, Faris Abdul Kareem (AL-Kindy College Medical Journal, 2012)
Objective The incidence of rhythm and conduction abnormalities during acute myocardial infarction may approaches 100%; most are seen during the pre-hospital and coronary care unit phases, leading to deleterious effect on morbidity and mortality, this study conducted to find important persistent dysrhythmia found during CCU admission of acute myocardial infarction patients.Method A retrospective observational study of 553 patients who were admitted to the Coronary Care Unit of Alkindy Teaching Hospital during Year 2011 with diagnosis of acute myocardial infarction, Information and data extracted from case sheets and associated 12 leads daily ECGsResults only 25% of our patients had dysrhythmia on examining the present 12 leads ECGs , the mean age are 64 years and 24% of female and 26% of male had dysrhythmias. Those with dysrhythmia had more shortness of breath and less chest and epigastric pain.. There is no relation of dysrhythmia to diabetes , hypertension or smoking. dysrhythmia associate inferolateral and anterolateral myocardial infarction more than anterior, lateral or inferior infarction.conclusion dysrhythmia in acute myocardial infarction, old age people had more dyrhythmia but gender had no effect, chest pain and shortness of breath also associate dysrhythmia significantly. Hypertension, diabetes ,and site of infarction had no effect on development of dysrhythmias, while size of infarction had significant effect.Key words; kindy, infarction, dysrhythmia